Batrachochytrium dendrobatidis infecting anurans in a protected area from Santa Fe province, Argentina - Ghirardi, Romina (2014)
The finding of anurans infected with Bd in a protected area in the floodplain of Paraná river makes imperative alert environmental authorities to take the necessary actions to evaluate the presence of the chytrid fungus in all species inhabiting islands of the PNISF. It is compulsory to take precautions to avoid the diffusion of this dangerous pathogen (Federici et al., 2008). In particular, rangers patrol in PNISF or scientist studying in the area should pay special attention not to transfer the zoospores from site to site, using different tools or disinfecting them accurately before moving between sites (see Livo, 2004 and Perotti y Ghirardi, 2010). Further environmental monitoring, combined with proper methods of quarantine and pathogen elimination are badly needed to guarantee amphibian survival and to prevent the spread of chytridiomycosis in this recently created protected area.